The Relationship Between Nurse Staffing, Quality, And Financial Performance In Hospitals - Shin, Dong Yeong; Weech-Maldonado, Robert; Chang, Jongwha (Archives of Business Research, 2020)
Little evidence exists the relationship of nurse staffing and quality with financial performance in hospitals. This study aimed to measure the relationship between nurse staffing, quality of care, and profitability in hospitals. This study used longitudinal panel datasets from 2006 to 2010, drawn from various datasets including the American Hospital Association Annual Survey Database, Medicare Cost Report, and Hospital Compare Data. This study used the random-effects linear regression model to measure the relationship between nurse staffing, quality, and profitability. In addition, we tested a mediating effect of quality on the relationship between nurse staffing and profitability. This study found nurse staffing’s significant association with quality and profitability in hospitals. First, compared to hospitals in the lowest quintile of RNs per 1,000 inpatient days, hospitals in the higher quintiles had lower pneumonia readmission rates, and higher total profit margins, operating margins, and cash flow margins. In addition, hospitals with lower pneumonia readmission rates were found to have higher total profit margins and cash flow margins. Lastly, the current study found that the positive relationship between RNs per 1,000 inpatient days and total profit margin and cash flow margin was partially mediated by pneumonia readmission rates. In conclusion, our finding that nurse staffing is positively associated with both quality of care and profitability in hospitals suggests that the idea of hospitals responding to financial pressures by cutting RN resources with a goal of greater profitability should be called into question. The influence of lower RN staffing levels on higher profitability for hospitals is uncertain, while it is possible that RN staff reductions may compromise the quality of patient care.